Highly efficient proliferation and regeneration of protocorm-like bodies (PLBS) of the threatened orchid, Phalaenopsis bellina - Chew, Yee-Chern; Muhammad Husni Abd Halim,; Wan Muhamad Asrul Nizam Wan Abdullah,; Janna Ong Abdullah,; Lai, Kok-Song (Penerbit Universiti Kebangsaan Malaysia, 2018)
Phalaenopsis bellina is an important indigenous fragrant orchid threatened with extinction. In this study, we evaluated the effect of medium strength, sucrose, nitrogen (NH4NO3) and potato extract on proliferation of P. bellina protocorm-like bodies (PLBs) to improve micropropagation in this species. Optimal treatment for PLBs proliferation rate with an average fresh weight (FW) of 0.97±0.16 g was obtained through culturing on half strength (½) MS medium containing 20 g/L sucrose, 15 mM NH4NO3 and 20% w/v potato extract supplemented with 0.8 μM 2,4 dichlorophenoxyacetic acid (2,4-D). The optimal treatment produced large, healthy and greenish PLBs with reduction in the occurrence of culture browning. In contrast, treatments with high potato extract (>20% w/v) or NH4NO3 (>30 mM) concentrations tend to have inhibitory effect and resulted in low PLBs proliferation rate, with an average FW of 0.77±0.15 g and 0.69±0.15 g, respectively. Plant regeneration of PLBs was achieved on plant growth regulator (PGR)-free ½ MS medium. In total, 60 healthy PLBs from the optimal treatment were successfully regenerated, acclimatized with 100% survival percentage and grew well in a mixture of soil, sand and vermicompost (8:4:2 (w/w/w)). With the optimal treatment, PLBs proliferation rate was enhanced by 27.63%. Our findings offer an improved micropropagation protocol of the endangered P. bellina for conservation and commercial production.